Biddulph Phillipps Reads William Cobbett or 19th Century Catholic Convert Reads 19th Century Political Journalist and Follows His Advice and Endows Monasteries: A Tale for a Wintry Day. (22nd October 2020) - McGowan, Beth
Abstract: Written in the 1820s, William Cobbett's book, A History of the Protestant Reformation in England and Ireland, defended medieval Catholicism primarily to criticize his contemporaries' treatment of the poor. A few decades later, members of the Oxford Movement would also defend medieval English Catholicism. The results of that revaluation of a Catholic past led some adherents of the movement to convert to Roman Catholicism, others to transform part of the English State Church into something that closely resembled Roman Catholicism and that was known as Anglo-Catholicism. A lesser known participant of the Oxford Movement, Robert Biddulph Phillipps, owned a copy of Cobbett's History and wrote extensively within the covers and pages of his copy of the book. This article traces the trajectory of the Phillipps's life, the history of the volume's ownership, and the views Phillipps expressed about Cobbett within its covers.